Observations of bromine monoxide transport in the Arctic sustained on aerosol particles - Peterson, Peter K.; Pöhler, Denis; Sihler, Holger; Zielcke, Johannes; General, Stephan; Frieß, Udo; Platt, Ulrich; Wagner, Thomas (Atmospheric chemistry and physics. Discussions, 2017)
The return of sunlight in the polar spring leads to the production of reactive halogen species from the surface snowpack, significantly altering the chemical composition of the Arctic near-surface atmosphere and the fate of long-range transported pollutants, including mercury. Recent work has shown the initial production of reactive bromine at the Arctic surface snowpack; however, we have limited knowledge of the vertical extent of this chemistry, as well as the lifetime and possible transport of reactive bromine aloft. Here, we present bromine monoxide (BrO) and aerosol particle measurements obtained during the March 2012 BRomine Ozone Mercury EXperiment (BROMEX) near Utqiaġvik (Barrow), AK. The airborne differential optical absorption spectroscopy (DOAS) measurements provided an unprecedented level of spatial resolution, over 2 orders of magnitude greater than satellite observations and with vertical resolution unable to be achieved by satellite methods, for BrO in the Arctic. This novel method provided quantitative identification of a BrO plume, between 500m and 1km aloft, moving at the speed of the air mass. Concurrent aerosol particle measurements suggest that this lofted reactive bromine plume was transported and maintained at elevated levels through heterogeneous reactions on colocated supermicron aerosol particles, independent of surface snowpack bromine chemistry. This chemical transport mechanism explains the large spatial extents often observed for reactive bromine chemistry, which impacts atmospheric composition and pollutant fate across the Arctic region, beyond areas of initial snowpack halogen production. The possibility of BrO enhancements disconnected from the surface potentially contributes to sustaining BrO in the free troposphere and must also be considered in the interpretation of satellite BrO column observations, particularly in the context of the rapidly changing Arctic sea ice and snowpack.